Advanced imaging-enabled understanding of cell wall remodeling mechanisms mediating plant drought stress tolerance - Zhao, Nannan; Zhou, Zhiguo; Cui, Shunli; Zhang, Xinye; Zhu, Shu; Wang, Ying; Zenda, Tinashe; Wenjing, Li (Frontiers in Plant Science, 2025)
Drought stress causes peculiar challenges to plant cells reliant on turgor pressure and a polysaccharides-enriched cell wall for growth and development. Appropriate cell wall changes in mechanical properties and biochemical composition under stress conditions constitute an indispensable stress adaptation strategy. A better understanding of stress-induced cell wall modifications is not only crucial for accruing fundamental scientific knowledge in plant biology, but will help us design novel strategies for enhancing crop drought tolerance. Here, we extensively reviewed how selected cell wall remodeling mechanisms, including cell wall demethylesterification, cell wall loosening and stiffening, stomata guard cell wall adjustment, cell wall lignification and root cell wall suberization orchestrate plant drought tolerance, revealing a potential target area for drought tolerance improvement in crops. Stress-induced demethylesterification of pectins, mediated by pectin methylesterases, permits calcium crosslinking of polyphenolics, which enhances cell wall rigidity and may help in intra-cell water preservation. Cell wall proteins such as xyloglucan endotransglucosylases/hydrolase, β-glucanases and expansins are regulated by drought stress, and orchestrate cell turgor-driven cell expansion, through modulating the loosening of cell wall polysaccharides, enabling cell and organ growth under those conditions. Meanwhile, overexpression of certain cell wall proteins/genes such as expansins may promote drought tolerance by improving cell water retention, antioxidant capacity, water use efficiency, and osmotic adjustment. We also discuss the genetic, transcriptional, and phytohormonal regulations of cell wall remodeling. Further, we highlight the recent advancements in elucidation of plant cell wall biosynthesis as aided by cutting-edge high-resolution imaging techniques that now facilitate direct visualization and quantitative in-situ (real-time) microanalysis of cell wall chemical composition and dynamics. Integrating latest cell wall imaging techniques to innovative single-cell omics, genome editing, and advanced data analysis approaches could facilitate appropriate cell wall modifications necessary for drought tolerance engineering in crop plants.